Screening for the causes of refractory hypoxemia in critically ill patients: A case report - Liu, Wanglin; Ding, Xin; He, Huaiwu; Long, Yun; Cui, Na (Frontiers in Medicine, 2022)
Hypoxemia was a very common symptom in critical patients and should be treated immediately before resulting in permanent organ failure. Rapid diagnosis of the etiology of hypoxemia could be achieved by combining the use of various bedside and radiation-free techniques such as lung ultrasound, electrical impedance tomography and echocardiography. By presenting a case of serious acute refractory hypoxemia, we proposed an efficient protocol for diagnosing and treating hypoxemia in a safe and fast way.